Detecting the depth of weak layer in concrete using R-wave dispersion techniques. (September 2018) - Tsai, Wen-Hsiang; Lin, Yiching; Cheng, Chia-Chi
Abstract: This study used the dispersion of R-waves in layered structures to detect the thickness of the deteriorated concrete surface layer. This study employed the mechanical impact to generate stress waves in tested objects. A receiver was placed on the impacted surface to record surface displacements caused by the arriving waves, which were subsequently fed into Morlet Wavelet Transform (MWT) to convert the displacement waveforms into spectrograms to observe R-wave dispersion characteristics. This study first conducted numerical analysis to assess the feasibility of the research concept; numerical models with a surface deteriorated layer of 30, 50, and 70 mm in thickness were employed to explore the influence of bottom surface reflection, contact time of impact, and receiver locations. Subsequently, experiments were carried out on concrete specimens containing weak layers to verify the numerical analysis results. Both the numerical and experimental results revealed that when the receivers were sufficiently far from the point of impact, dispersion occurs among the R-waves propagating along the deteriorated surface layer because R-wave velocity increases with wavelength. Furthermore, the dispersion curves all exhibit a turning point that signifies the rapid increase in wave velocity with wavelength, and this turning point corresponds to a wavelength that is approximately 1.7 times the thickness of the deteriorated layer. This is an effective rule for estimating the deteriorated layer's thickness.